Characteristics of resistance training-based protocols in older adults with sarcopenic obesity: a scoping review of training procedure recommendations - Silva, Leonardo Santos Lopes da; Gonçalves, Leonardo da Silva; Abdalla, Pedro Pugliesi; Benjamim, Cícero Jonas Rodrigues; Tasinafo, Márcio Fernando; Venturini, Ana Cláudia Rossini; Bohn, Lucimere; Mota, Jorge; Marcos-Pardo, Pablo Jorge; Kemmler, Wolfgang; dos Santos, André Pereira; Machado, Dalmo Roberto Lopes (Frontiers in Nutrition, 2023)
Sarcopenic obesity (SO) is a clinical and functional disease characterized by the coexistence of obesity and sarcopenia. Resistance training (RT) characteristics for older adults with sarcopenia or obesity are already well-established in the scientific literature. Nonetheless, we still do not know how detailed the RT protocols are described for older adults with SO. Therefore, we aimed to analyze the characteristics of RT programs, including each of its variables, recommended for older adults with SO. This is a scoping review study that was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis for Scoping Reviews. The search was carried out until November 2022, in PubMed/MEDLINE, EMBASE, Cochrane Library, Web of Science, Scopus, LILACS, Google Scholar, and medRxiv databases. The studies should be included SO diagnosis and RT as an intervention strategy. The RT variables analyzed were: exercise selection, the volume of sets, the intensity of load, repetition cadence, rest interval between sets, and weekly frequency. 1,693 studies were identified. After applying the exclusion criteria, 15 studies were included in the final analysis. The duration of the RT intervention ranged from eight-24 weeks. All studies included full-body routines, with single/multi-joint exercises. Regarding the volume of sets, some studies fixed it in three sets whereas others varied between one-three sets. The load was reported by repetitions range and weight-lifted, by elastic-band color/resistance, percentage of one repetition maximum, or perceived exertion scale. Repetition cadence was fixed in some studies, while it was self-selected between concentric and eccentric-phases in others. The interval between sets of rest varied from 30-180 seconds. All studies reported progression overload during the interventions. Not all studies reported how was made the exercise selection, repetition cadence, and rest interval. The characteristics of RT protocols and their variables prescribed in the literature for older adults with SO were mapped. The lack of detail on some training variables (i.e., exercise selection, repetition cadence, and rest interval) was identified. RT protocols are heterogeneous and described only partially among studies. Recommendations for RT prescription details in older adults with SO are provided for future studies. https://osf.io/wzk3d/